HUBUNGAN TINGKAT KECUKUPAN ENERGI DAN ZAT GIZI MAKRO DENGAN KETAHANAN PANGAN SISWA SEKOLAH DASAR DARI KELUARGA PETANI [Correlation of Energy and Macronutrient Adequacy Level and Food Security among Elementary School Children from Farmers Family] - Nur Fatimah; Triska Susila Nindya (Universitas Airlangga, 2019)
Food security is an underlying cause of malnutrition in children. Food security affects children’s quality and quantity of food consumption. Food quantity are refl ected by energy and macronutrient adequacy level (protein, fat, carbohydrate). This study aimed to analyze the association between the energy and macronutrient adequacy level with food security among elementary school children from farmer family. Study was a cross sectional study with simple random sampling. Total samples are 60 elementary school students from grade 1 to 6 at SDN Jombatan 1, SDN Jombatan 2, and SDN Jombatan 3 Jombatan Village, Kesamben Sub-district, Jombang Regency, and their parents are paddy rice farmers. Data collected by samples characteristics questionnaire, 2x24 hours food recall form, and United States – Household Food Security Survey Modul (US-HFSSM) questionnaire. Spearman correlation test were used to analyze the correlation between variables. Most of school children had insuffi cient energy and macronutrients adequacy level energy (91.7%), protein (54.2%), fat (84.8%), and carbohydrate (86.4%) respectively. More than half of farmer family were included in food insecurity without hunger (58.3%). There was signifi cant association between energy adequacy level with food security among elementary school students from farmer family (p=0.039). Nonetheless, there were no signifi cant correlation between macronutrient adequacy level such as protein (p=0.931), fat (p=0.189), and carbohydrate (p=0.104) with food security among elementary school student from farmer family. Family food security associated with the quantity of family food consumption. Increasing food security to increase energy adequacy level can be done by increasing income from non-agricultural sector.